Reception - Bulleid, Ann (Catering and hospitality., 1996)
Case studies - put students in real-life scenarios and help them learn how to react to them. Unit-by-unit, element-by-element approach with full coverage of the underpinning knowledge. A competence-based approach, complemented by activities and pointers, to enhance students' knowledge. Freestanding units allow students to select material according to their needs. 'Get ahead' sections at the end of each unit, encourage further learning and development.